Cultivating elok budi character value in elementary school - Elpri Darta Putra; Bunyamin Maftuh; Mamat Supriatna (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
Character education in primary schools is essential to shaping children's moral values and good behavior. This research uses the literature study method to understand how the character values of Eloklah Budi can be effectively applied in the daily lives of elementary school students. Data were obtained from various sources, such as books, journal articles, and educational policies, which were analyzed to describe practical approaches to integrating character values. The results show that character education focusing on the concept of